2007
DOI: 10.1021/jp068480p
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Physical Properties of CaWO4 Nanocrystals via Particle Size Control

Abstract: This work reports on a combinational methodology to CaWO4 nanocrystals of controllable particle sizes for comprehension of particle size dependences of physical properties. Citric acid as a capping molecule restricted the growth of CaWO4 nanocrystals and gave a small particle size of 3.6 nm at room temperature at pH 8, while large particle sizes or the absence of CaWO4 nanocrystals were always observed when the pH value was higher or lower than 8. Hydrothermal treatments over 3.6 nm CaWO4 at high temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
60
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 43 publications
9
60
0
2
Order By: Relevance
“…To verify this conclusion and to uncover the relevant physics, Errandonea and his co-workers [27] theoretically analyzed the volume dependence of the structural parameters in CaWO 4 nanoparticles that has been experimentally determined by Li and his group [23]. With the help of ab initio total-energy calculations, they concluded that the enhanced symmetry in CaWO 4 nanoparticles with particle size reduction is a consequence of the negative pressure exerted on the nanoparticles.…”
Section: Lattice Expansionmentioning
confidence: 91%
See 1 more Smart Citation
“…To verify this conclusion and to uncover the relevant physics, Errandonea and his co-workers [27] theoretically analyzed the volume dependence of the structural parameters in CaWO 4 nanoparticles that has been experimentally determined by Li and his group [23]. With the help of ab initio total-energy calculations, they concluded that the enhanced symmetry in CaWO 4 nanoparticles with particle size reduction is a consequence of the negative pressure exerted on the nanoparticles.…”
Section: Lattice Expansionmentioning
confidence: 91%
“…Inspired by these observations, Li and his co-workers continued to study the lattice variations in many other simple oxides [21,22] like ZnO and NiO, and found the similar lattice expansion -a seemly general law for oxide nanopartiles. To make sure the validity of this general law, Li and his research group also extended their findings to the complex oxide nanoparticles like MWO 4 (M = Ca, Cd, Mn) [23][24][25][26]. It was found that the lattice expansion is followed by systematic variations in lattice symmetry.…”
Section: Lattice Expansionmentioning
confidence: 94%
“…[13,14] Recently, there are increasing efforts devoted to the synthetic investigation of inorganic nano-particles. Various synthetic methods have been employed to prepare alkaline-earth tungstates, including solid-state reaction, [13] polymeric precursor, [18] Pechini, [19] hydrothermal, [14,20] sol-gel, [21] molten salt, [22] co-precipitation, [23] solvothermal, [24] combustion reaction [25] et al Various nano/micro-crystals with beautiful morphologies have been successfully fabricated, such as nanowires, nanotubes, [26] nanoparticles, [24,27] nanorods, [28] microspheres, [8] and hollow spheres. [29] However, in contrast to the extensive studies on shape-controlled syntheses, the structure characterization on alkaline-earth tungstates after RE-doping is rare.…”
Section: Introductionmentioning
confidence: 99%
“…O estudo e o desenvolvimento de determinados materiais semicondutores, com propriedades ópticas ativas como, por exemplo, propriedades fotoluminescentes, propriedades fotocatalíticas, eletroluminescência, propriedades ópticas não lineares vem sendo estudado diariamente pela comunidade científica [1,2]. Os molibdatos (MoO 4 2-) e os tungstatos (WO 4 2-), em especial o tungstato de cálcio (CaWO 4 ), são exemplos desses materiais.…”
Section: Introductionunclassified